Analisis Laras Bahasa pada Headline Surat Kabar Metro 24 - Padila, Elsa Duwi; Winarti, Winarti (Multiverse: Open Multidisciplinary Journal, 2023)
This study aims to provide a comprehensive description of the language tunings employed in the headlines of the newspaper Metro 24. It specifically focuses on identifying and analyzing the social problems addressed in these headlines. The research adopts a qualitative descriptive methodology to examine the linguistic features present in the selected headlines. Secondary data from the newspaper Metro 24 serves as the primary source for this study. The data analysis process involves collecting headlines from the newspaper Metro 24 and applying theoretical frameworks derived from relevant sources, such as books and scholarly papers. The findings reveal the existence of various language categories, including ordinary language, academic language, journalistic language, literary language, legal language, and religious language, within the headline texts. This study contributes to a better understanding of the linguistic aspects employed in newspaper headlines and sheds light on the social issues covered in the headlines of Metro 24. It serves as a valuable resource for linguists, journalists, and researchers interested in the analysis of headline language and its connection to societal matters.